Fundamental frequency estimation for heterophonical Turkish music by using VMD - (:unkn) unknown (IEEE, 345 E 47th St, New York, Ny 10017 USA, 2016)
In this study, a new method is presented for the fundamental frequency estimation of heterophonical Turkish makam music recordings that include percusssive instrument by using Variational Mode Decomposition (VMD). VMD is a method to decompose an input signal into an ensemble of subsignals (modes) which is entirely non-recursive and determines the relevant bands adaptively and estimates the corresponding modes concurrently. In order to decompose a given signal optimally, actuated by the narrow-band properties corresponding to the Intrinsic Mode Function definition used in Emprical Mode Decomposition (EMD), and we seek an ensemble of modes. Simulation results on fundamental frequency estimation of real music data show comparable performance to other common decomposition methods for music signals such as YIN and MELODIA based methods.
Keywords: Variational mode decomposition; heterophonical music; Turkish maqam music; fundamental frequency